A novel two-phase load compensation method under unbalanced voltages for renewable energy integration - Zhang, Yuanshi; Wang, Liwei; Struthers, Chris; Hu, Qinran (Frontiers in Energy Research, 2022)
This paper explores new design methods for correcting unbalanced power distribution networks in order to improve the power quality and reliability for sensitive industrial loads. While traditional compensators typically need to be connected to all the three phases of the AC network, this paper proposes a novel three-phase voltage balancing compensator that can operate with a connection to only two of the three phases. The new concept is based on the phasor symmetrical component theory, which can be implemented using either mechanically switched reactors (MSRs), TCRs (thyristor-controlled reactors) or VSCs (Voltage source converters). Three methods are presented to calculate the value of the proposed two-phase compensator, i.e. discrete solution, analytical solution and novel simplified solution. The discrete solution is solved via the exhaustive search method, which was successfully used by StruthersTech to correct the power quality of an unbalanced industrial power system. The analytical solution is based on the nodal voltage of analysis method. The simplified solution derives a practical albeit approximated relationship between the negative sequence source voltage and zero sequence load voltage, thus avoiding the need to solve nonlinear equations. Dynamic simulations are implemented using MATLAB/Simulink Simscape Blockset to validate the effectiveness of the proposed two-phase voltage balancing method.